Central mechanisms of auditory perception: neuroanatomical bases and clinical manifestations in dementia - ВОЛИНЕЦЬ, Володимир (Київський національний університет імені Тараса Шевченка, 2025)
Background. Hearing is one of the key sensory systems that enable adaptation to the environment, communication, learning, and cognitive integration. According to the World Health Organisation, over 1.5 billion people worldwide experienced hearing loss in 2019, including 430 million who required assistance. These numbers could rise to 2.5 billion and 700 million, respectively, by 2050. The study revealed that auditory perception has a structured neuroanatomical organisation, including ventral and dorsal sound processing pathways, functional asymmetry of the temporal lobes, and specialised modules for processing different elements of auditory messages. Hearing loss among both military personnel and civilians, as a result of full-scale invasion, is of particular concern due to its potential link to neurodegeneration and the development of dementias. Each profile of neurodegeneration manifests in distinct patterns of auditory-processing dysfunction resulting from damage to specific processing modules. The aim of the study was to contribute to the scientific discourse on the ongoing evolution of auditory perception research, analyse the cortical correlates of hearing impairment or loss, and explore the interrelationship between dementia and auditory disorders. Results. This theoretical review highlighted the challenges of early investigation of the auditory perception system due to its neuroanatomical redundancy, The frequent masking of auditory disorders as speech and language impairments, and the gradual shift from a continuous to a modular theory of sound processing. The review also outlined the cognitive architecture of auditory information processing and its modular organisation, and demonstrated a bidirectional relationship between dysfunction of the auditory system and diverse forms of dementia. Conclusions. It can be argued that auditory perception is a complex, modular system that is sensitive to neurodegenerative changes, particularly in the temporal lobe. Hearing loss is not merely a sensory issue but also a cognitive phenomenon that can serve as a predictor of dementia. Double dissociations and the interaction between peripheral and central components of hearing necessitate a multifactorial approach to diagnosis and intervention. Two areas of assistance are proposed: cognitive-compensatory (for the central effect of biological ageing) and sensory (for the central effect of peripheral pathology). Auditory therapy is considered a promising non-pharmacological method for improving the quality of life of individuals with dementia and hearing loss. One of the limitations is that the article is narrative and overview in nature, with no empirical research conducted by the author.

Вступ. Слух — одна з ключових сенсорних систем, що забезпечує адаптацію до середовища, комунікацію, навчання та когнітивну інтеграцію. За даними ВООЗ на 2019 рік, понад 1.5 млрд людей мають порушення слуху, з них 430 млн потребують допомоги. До 2050 року ці цифри можуть зрости до 2.5 млрд і 700 млн відповідно. У дослідженні було розкрито, що аудіальна перцепція має структуровану нейроанатомічну організацію, яка включає вентральні та дорзальні шляхи обробки звуку, функціональну асиметрію скроневих часток та спеціалізовані модулі для обробки різних елементів аудіального повідомлення. Погіршення слуху, як серед військових, так і серед цивільного населення внаслідок повномасштабного вторгнення, набуває особливого значення у зв’язку з його потенційним зв’язком із нейродегенерацією та розвитком деменцій. Кожний профіль нейродегенерації маніфестується у різноманітних формах дисфункції системи аудіальної перцепції, внаслідок ураження специфічних модулів обробки. Метою дослідження було введення у науковий дискурс особливостей континуального розвитку досліджень аудіальної перцепції, аналіз кортикальних корелятів погіршення або втрати слуху та взаємозв’язку деменцій з розладами слуху. Результати. Внаслідок проведеного теоретичного дослідження, було окреслено проблематику раннього вивчення системи аудіальної перцепції внаслідок її нейроанатомічної надмірності, маскування аудіальних розладів під розлади мовлення та поступовий перехід від континуальної теорії обробки слухового сигналу до модульної. Висвітлено елементи когнітивної системи обробки аудіальної інформації та її модульну структуру. Показано двосторонній зв’язок ураження системи аудіальної перцепції та деменцій різного походження. Висновки. Внаслідок проведеного дослідження, можна аргументувати, що аудіальна перцепція є складною, модульною системою, чутливою до нейродегенеративних змін, особливо в скроневій частці. Втрата слуху — не лише сенсорний, а й когнітивний феномен, що може виступати предиктором деменцій. Подвійні дисоціації та взаємодія периферичних і центральних компонентів слуху вимагають мультифакторного підходу до діагностики та втручання. Запропоновано два напрями допомоги: когнітивно-компенсаторний (при центральному ефекті біологічного старіння) та сенсорний (при центральному ефекті периферичної патології). Аудіальна терапія розглядається як перспективний немедикаментозний метод покращення якості життя осіб із деменцією та втратою слуху. Одним з обмежень виступає те, що стаття носить наративний оглядовий характер, емпіричне дослідження автора відсутнє.
Центральні механізми аудіальної перцепції: нейроанатомічні основи та клінічні прояви при деменціях
Keywords: hearing impairments; double dissociation; temporal lobe; cognitive ageing; neurodegeneration; розлади слуху; подвійна дисоціація; скронева частка; когнітивне старіння; нейродегенерація